2017
DOI: 10.1016/j.jtho.2016.11.483
|View full text |Cite
|
Sign up to set email alerts
|

MA13.07 Tumor-Targeted Radiation Promotes Abscopal Efficacy of Regionally Administered CAR T Cells: A Rationale for Clinical Trial

Abstract: annotated by The Cancer Genome Atlas lung ACA dataset and all hypermorphic mutations identified were located in the highly conserved kinase domain. The majority of mutations have been known to enhance kinase activity in melanoma in a fashion analogous to the well-known BRAF V600E mutation. In line with these findings, we showed that kinase domain mutations were hypermorphic as measured by MEK and ERK1/2 phosphorylation. We also showed that exposure of wild type BRAF cells to radiation results only in a transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also, intrapleural delivery of cancer‐antigen mesothelin targeted CAR‐T cells were administered to a murine model with prior focal thoracic XRT which elicited a systemic abscopal response as well. This is yet to see potential in the clinical space at this time 66 …”
Section: Abscopal Effects In Systemic Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…Also, intrapleural delivery of cancer‐antigen mesothelin targeted CAR‐T cells were administered to a murine model with prior focal thoracic XRT which elicited a systemic abscopal response as well. This is yet to see potential in the clinical space at this time 66 …”
Section: Abscopal Effects In Systemic Therapymentioning
confidence: 98%
“…This is yet to see potential in the clinical space at this time. 66 One of the earliest preclinical studies demonstrated synergy when IL-15 which facilitates release of effector T cells and NK cells, and ionizing radiation potentiated a cellular mediated immune response in the tumor and systemic circulation. Addition of DTA-1 which is a glucocorticoid-induced tumor necrosis factor receptorrelated protein agonist sustained this response longer.…”
Section: Cellular Therapymentioning
confidence: 99%
“…Preclinical investigations have demonstrated potential immune responses following radiation therapy and augmentation of these responses by combining with immunotherapeutic agents (62). We have reported that a single dose of thoracic radiation prior to administration of CAR T cells has improved survival outcomes in a preclinical MPM model (63). More mechanistic insights into these combination therapy approaches will help translate benefits to mesothelioma patients.…”
Section: Combination Immunotherapiesmentioning
confidence: 99%
“…In the RT group, the pleural tumor was irradiated with a single sub-therapeutic RT dose prior to CAR T cells injection. Locally-injected CAR T cells promoted the abscopal effect in distant tumor sites, and this effect was potentiated via RT [98].…”
Section: Abscopal Effectsmentioning
confidence: 99%